Picosecond orientational dynamics of water in living cells. Issue 1 (December 2017) - Tros, Martijn; Zheng, Linli; Hunger, Johannes; Bonn, Mischa; Bonn, Daniel; Smits, Gertien J.; Woutersen, Sander
Abstract Cells are extremely crowded, and a central question in biology is how this affects the intracellular water. Here, we use ultrafast vibrational spectroscopy and dielectric-relaxation spectroscopy to observe the random orientational motion of water molecules inside living cells of three prototypical organisms:Escherichia coli, Saccharomyces cerevisiae (yeast), and spores ofBacillus subtilis . In all three organisms, most of the intracellular water exhibits the same random orientational motion as neat water (characteristic time constants ~9 and ~2 ps for the first-order and second-order orientational correlation functions), whereas a smaller fraction exhibits slower orientational dynamics. The fraction of slow intracellular water varies between organisms, ranging from ~20% inE. coli to ~45% inB. subtilis spores. Comparison with the water dynamics observed in solutions mimicking the chemical composition of (parts of) the cytosol shows that the slow water is bound mostly to proteins, and to a lesser extent to other biomolecules and ions. The cytoplasm's crowdedness leads one to expect that cell water is different from bulk water. By measuring the rotational motion of water molecules in living cells, Tros et al. find that apart from a small fraction of water solvating biomolecules, cell water has the same dynamics as bulk water.